Technical Variables Affecting to Production of Pickle Ficus (Ficus Racemosa) - Nguyen Phuoc Minh (Journal of Global Pharma Technology, 2019)
The plant Ficus racemosa occupies a vital place in the traditional system of medicines. It contains antioxidants which quenches free radical damage to cells and tissues. The short shelf life of ficus can be a major cause of postharvest losses especially during peak harvesting season. Fermentation is one of the most convenient technologies for the production of shelf stable food product. The objective of this study was to evaluate different variables influencing to the fermentation of ficus such as concentration of CaCl2, temperature and time for blanching; effect of ratio Lactobacilus acidophillus to the antioxidant of fermented ficus. Results showed that ficus should be blanched in hot water 95oC in 15 seconds with the present of 3.0% CaCl2. Moreover, the fermentation process for pickle ficus had the best antioxidant by addition of 15% sugar, Lactobacilus acidophillus at ratio 2.0 x 108 cells/ml. Blanching and fermentation had significantly affected to antioxidant capacity and firmness of pickle ficus. The pickle ficus had a high content of antioxidant as well as firmness. This plant holds a great prospective source for developing herbal products and thus a vital source of income for the pharmaceutical industry.Keywords: Ficus, pickle, fermentation, blanching, Lactobacilus acidophillus, antioxidant.